2017
DOI: 10.1103/physrevb.96.060506
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic thermomagnetic avalanche activity in field-cooled superconducting films

Abstract: The electrodynamic behavior of isotropic superconducting Nb films cooled below their critical temperature in the presence of in-plane applied magnetic fields is investigated using magneto-optical imaging. A specially designed local flux injector is used to show that the frozen-in in-plane vortices strongly guide and enhance the penetration of perpendicular vortices, whereas their penetration across the array of in-plane vortices is essentially unchanged. This result provides the key to understanding why field-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
2
7
0
2
Order By: Relevance
“…In addition to the clear difference in the flux penetration depth from the two pairs of opposite edges, the image also reveals that the penetration has a clear filamentary character in the direction parallel to the frozen-in flux. This suggests that the motion of incoming perpendicular vortices is facilitated and guided by the in-plane vortices already present in the film, an observation fully consistent with MOI results reported recently [25]. In that work it was found that in terms of critical current densities the in-plane magnetic field has little influence on the magnitude of J L c .…”
Section: A Flux Penetration At 7 Ksupporting
confidence: 89%
See 1 more Smart Citation
“…In addition to the clear difference in the flux penetration depth from the two pairs of opposite edges, the image also reveals that the penetration has a clear filamentary character in the direction parallel to the frozen-in flux. This suggests that the motion of incoming perpendicular vortices is facilitated and guided by the in-plane vortices already present in the film, an observation fully consistent with MOI results reported recently [25]. In that work it was found that in terms of critical current densities the in-plane magnetic field has little influence on the magnitude of J L c .…”
Section: A Flux Penetration At 7 Ksupporting
confidence: 89%
“…Interestingly, this image shows that the incipient stage of the runaway has a flux distribution quite different from that created by a current pulse at 7 K. The penetrated region has at 7 K the shape of a semicircle with radius close to the width of the legs of the injector. [25]. In Fig.…”
Section: Quenching Of Dendritesmentioning
confidence: 98%
“…We have observed further that preplacement of magnetic flux with a two-step PFM technique may reduce the generation of heat, and hence moderate the extent of the region of instabilities. This reflects partly how the frozen-in vortices affect the magnetization of bulk samples [32].…”
Section: Introductionmentioning
confidence: 99%
“…A Fig.6.11 mostra a dependência genérica do campo magnético perpendicular limiar em função da corrente crítica para filmes supercondutores, onde pode-se observar que o fato de termos um incremento no campo limiar para o começo de avalanches de vórtices implica na diminuição da densidade de corrente crítica no supercondutor. Dessa forma, podemos afirmar que a presença de nanofios magnéticos na matriz porosa estaria contribuindo para a diminuição da corrente Figura 6.11: Curva genérica do campo perpendicular limiar para o inicio de avalanches termomagnéticas num filme supercondutor em função da densidade de corrente crítica [137,138]. crítica no filme supercondutor.…”
Section: Resultados Das Imagens Por Magneto-óticaunclassified
“…. 110 6.11 Curva genérica do campo perpendicular limiar para o inicio de avalanches termomagnéticas num filme supercondutor em função da densidade de corrente crítica [137,138]…”
Section: Introductionunclassified